Determining the level of dustiness in the grain harvesting elevator - Labzhynska, Мargaryta; Volodchenkova, Natalia (My University, 2017)
The paper describes the experimental data on the level of dust in the silo. The concentrations of dust in the breathing zone of workers of various industrial facilities. The studies were conducted by weight, the essence of which is to determine the difference in mass of the filter before and after passing through it a specified volume of air. Dust concentration was determined in mg / m3 calculation method.
Keywords: кафедра екології та екоменеджменту; working conditions; air of working area; dust; умови праці; повітря робочої зони; пил; условия труда; воздух рабочей зоны; пыль